Diplomatics in China. (16th March 2015) - Pan, Weimei
Abstract : Purpose: – This paper aims to explore if there is an analogous discipline in China to diplomatics. Design/methodology/approach: – A comparison method is used for the exploration. Five Chinese disciplines are chosen for the comparison, which are Wenxian xue, Bianwei xue, Dangan jianbian xue, Wenshu xue and Gu wenshu xue . The diplomatics, as discussed in this paper, is modern diplomatics, as exemplified in the work of Dr Luciana Duranti. Findings: – It was found that while there is no such Chinese discipline identical to diplomatics, its knowledge is distributed among several Chinese disciplines. This indicates the common concern and efforts in the West and East and the potential for the further development of diplomatics as a global discipline. Research limitations/implications: – The disciplines this paper has examined are what this author is aware of that share certain similarities with diplomatics and the discussion is based on this author's understanding; thus, it is possible that there are disciplines that this author did not know or the understanding is insufficient to reveal all the connections between diplomatics and these disciplines. Further research from other perspectives might be needed. Originality/value: – To the author's best knowledge, this is the first paper in English comparing Chinese diplomatic disciplines with diplomatics. It has also shed some light on the development of several Chinese disciplines.